Control of Hsp90 chaperone and its clients by N-terminal acetylation and the N-end rule pathway - Jang‐Hyun Oh; Ju-Yeon Hyun; Alexander Varshavsky (2017)
Significance We found that the yeast Hsp90 chaperone system is greatly impaired in naa10Δ cells, which cannot N-terminally acetylate a majority of normally N-terminally acetylated proteins, including Hsp90 and its cochaperones. Hsp90 clients, including Chk1, Kar4, Tup1, Gpd1, Ste11, and even the Hsp90 chaperone (Hsc82) itself, became short-lived substrates of the Arg/N-end rule pathway in naa10Δ cells. Ubr1 targets the Chk1 kinase through its internal degron. Interactions of Hsp90 with Chk1 could be detected in wild-type but not in naa10Δ cells. These results revealed a major role of N-terminal acetylation in the Hsp90-mediated protein homeostasis and showed that a number of Hsp90 clients are previously unknown substrates of the Arg/N-end rule pathway.